Presenting a model for predicting women's sexual performance based on childhood trauma with the mediating role of sexual self-concept - Saberi , Hayideh; Salahian, Afshin; Amiri, Mona (Psychology of Woman Journal, 2021)
This research predicts women's sexual performance based on childhood traumas and the role of sexual self-concept. The current research design was a correlation design through structural equation modeling, and the statistical population included non-random samples from the cities of Tehran and Karaj. Rosen's (2000) women's sexual performance questionnaires, Bernstein's (1988) childhood traumas, and Schmidt's (2000) sexual self-image were used as measurement tools. Data analysis was done by SPSS-24 and AMOS-26 software. The results indicated that the main hypothesis that predicts women's sexual performance based on childhood traumas, considering the role of sexual self-concept as a mediating factor, has sufficient fit. Childhood traumas not only have a profound effect on women's sexual self-image but also disrupt their sexual performance. Because the psychological insecurity of childhood provides a bed of lack of trust in important people in life and romantic and emotional relationships, therefore, during sexual intercourse, this lack of trust prevents the expression of one's feelings and needs, and one may even inhibit one's enjoyment of the relationship and finally reach sexual dissatisfaction.